Música, decolonialidade e ensino de história: perspectivas a partir do rap indígena - Faria, Aurélio Inácio (2022)
The dissertation has as its object of study the use of music in teaching indigenous history. It proposes the use of rap for the study of indigenous themes in the teaching of history of basic education, from the perspective of decolonial studies. It aims to identify the state of the art in studies related to the teaching of history and the use of music as well as indigenous themes in ProfHistória, evaluating its possibilities among different languages, focusing on the potential of indigenous rap as a didactic-methodological instrument and content generator center. The intention is to contextualize a differentiated proposal for the use of indigenous themes in history teaching based on decolonial studies to assist in the knowledge and appreciation of indigenous history, in addition to sensitizing students about the importance of studying indigenous themes and giving visibility to this culture through music. From the discussions carried out in a literature review, the propositional part will involve a didactic booklet with guidelines and suggestions for teachers, as well as intertextual studies and reflections to be applied together to students involving the use of indigenous rap. The didactic proposal has the specific purpose of providing history teachers with a suitable teaching material to think about the approach to indigenous themes through music (indigenous rap), in accordance with the prerogatives proposed from the “Law 11.645/2008” and of decolonial debates.